Ecosystem stability of temperate grasslands in response to variability of hydrological conditions - Lara, Bruno; Vercelli, Natalia; Entraigas, Ilda; Scaramuzzino, Rosa; Gandini, Marcelo; Salese, Sofía; Goyenetche, Juan Manuel (Austral ecology, 2023)
The relationship between biodiversity and the stability of ecosystem functioning over time has been widely studied. The current global context has refloated this topic for biodiversity's role in buffering the effects of different disturbances. In general, the results of these studies show that ecosystem functioning is more stable over time in more diverse systems. However, these results are derived from empirical research on small‐scale studies, where species and disturbances conditions are manipulated. In this work, we used climate and floristic information data obtained from surveys over an extended period on Flooding Pampa grasslands (Argentina) with a remotely sensed indicator of the stability of net primary productivity at a regional scale over a broad temporal range to evaluate the relationship between species diversity and the stability of ecosystem functioning under different water conditions. We found a close correlation between Normalized Difference Vegetation Index responses of natural grasslands and climate variability in the study area. Besides, grasslands with higher species richness and diversity showed greater stability in ecosystem functioning at different water conditions. The results obtained could be relevant in natural resource management for the close relationship between diversity–stability in a local and regional productive context characterized by a simplified landscape of space and time. We analyze the relationship between species diversity and the stability of net primary productivity in natural grasslands of the Flooding Pampa (Argentina) subject to climate variability at broad spatiotemporal scales using information derived from remote sensing with climate and floristic information data